Identity Negotiation in Recovering Addicts Who Work as Addiction Counselors (Phenomenological Study on the Indonesian Addiction Counselors Association North Sumatra Region) - Simbolon, Meydita Asima Megarani; Zulkarnain, Iskandar; Ridho, Hatta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the experience of social stigma experienced by recovering addicts before working as addiction counselors, analyze the rocess of negotiating the identity of recovering addicts who work as addiction counselors, and analyze the results of negotiating the identity of recovering addicts who work as addiction counselors. The theory used is identity negotiation coined by Stella Ting-Toomey to analyze the process and results of identity negotiation in social interaction. This research was conducted using a qualitative approach with a phenomenological method. Data collection techniques were carried out by in-depth interviews and passive participation observation. Informants were taken until data saturation and totaled five people. The results showed that the stigma experienced by recovering addicts before working as addiction counselors was that they were considered criminals, community trash, still drug addicts and family burdens so that recovering addicts received discrimination, were shunned and had difficulty finding work. The process of negotiating the recovering addict's identity in this study is by increasing knowledge about the world of counseling and rehabilitation, raising awareness of the motivation to become an addiction counselor and strengthening social interaction skills through effective communication strategies. The results of negotiating the identity of recovering addicts who work as addiction counselors are feelings of being understood, valued and supported by others. Process of negotiating the identity of recovering addicts who work as addiction counselors, and analyze the results of negotiating the identity of recovering addicts who work as addiction counselors. This research was conducted using a qualitative approach with a phenomenological method. Data collection techniques were carried out by in-depth interviews and passive participation observation. The subjects in this study are recovering addicts who have worked as addiction counselors for at least four years and are members of the IKAI North Sumatra professional organization. Informants were taken until data saturation and totaled five people. The results showed that the stigma experienced by recovering addicts before working as addiction counselors was that they were considered criminals, community trash, still drug addicts and family burdens so that recovering addicts received discrimination, were shunned and had difficulty finding work. The process of negotiating the recovering addict's identity in this study is by increasing knowledge about the world of counseling and rehabilitation, raising awareness of the motivation to become an addiction counselor and strengthening social interaction skills through effective communication strategies. The results of negotiating the identity of recovering addicts who work as addiction counselors are feelings of being understood, valued and supported by others